2004
DOI: 10.1037/1040-3590.16.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Education-Stratified Base-Rate Information on Discrepancy Scores Within and Between the Wechsler Adult Intelligence Scale-Third Edition and the Wechsler Memory Scale-Third Edition.

Abstract: The Wechsler Adult Intelligence Scale--Third Edition (WAIS-III; D. Wechsler, 1997a) and the Wechsler Memory Scale--Third Edition (WMS-III; D. Wechsler, 1997b) are 2 of the most frequently used measures in psychology and neuropsychology. To facilitate the diagnostic use of these measures in the clinical decision-making process, this article provides information on education-stratified, directional prevalence rates (i.e., base rates) of discrepancy scores between the major index scores for the WAIS-III, the WMS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…These findings have significant implications for diagnostic accuracy, as individuals with lower IQ levels have a higher risk for false-negative errors, and individuals at higher IQ levels have a higher risk for false-positive errors in identifying acquired memory decline. Similar findings have been reported for discrepancies between individual index scores of the WMS-III and WAIS-III when stratified by educational level (Dori & Chelune, 2004). Patton and colleagues (Patton et al, 2006) also identified a similar pattern of discrepancies between the Total Scale score and individual indices on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS; Randolph, 1998) with older adults.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…These findings have significant implications for diagnostic accuracy, as individuals with lower IQ levels have a higher risk for false-negative errors, and individuals at higher IQ levels have a higher risk for false-positive errors in identifying acquired memory decline. Similar findings have been reported for discrepancies between individual index scores of the WMS-III and WAIS-III when stratified by educational level (Dori & Chelune, 2004). Patton and colleagues (Patton et al, 2006) also identified a similar pattern of discrepancies between the Total Scale score and individual indices on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS; Randolph, 1998) with older adults.…”
Section: Introductionsupporting
confidence: 52%
“…Additional studies have established differential base-rates of discrepancies with varying levels of pre-morbid functioning (Dori & Chelune, 2004;Hawkins & Tulsky, 2001;Matarazzo & Herman, 1985;Patton et al, 2006). Few studies have examined base-rates of cognitive discrepancies in children.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Asymmetric cognitive profiles can capture relative intraindividual differences by comparing performance on dissimilar neuropsychological tests or domains such as verbal relative to visuospatial abilities. Infrequent or atypical performance discrepancies may signal a neurodegenerative process and are frequently used in both clinical and research settings to identify potential changes from premorbid levels of cognitive functioning (Dori and Chelune 2004;Lange and Chelune 2006;Wilde et al 2001). Thus, asymmetric cognitive profiles may have utility for detecting a prodromal phase of AD for a number of reasons.…”
Section: Cognitive Discrepancy Studiesmentioning
confidence: 98%